Nanoparticles for Thrombolytic Therapy in Ischemic Stroke: A Systematic Review and Meta-Analysis of Preclinical Studies - Jesús Prego-Domínguez; Fernando Laso-García; Nuria Palomar-Alonso; María Pérez-Mato; Esteban López-Arias; Antonio Dopico-López; Pablo Hervella; María Gutiérrez-Fernández; María Alonso de Leciñana; Ester Polo; Beatriz Pelaz; Pablo del Pino; et al. (Pharmaceutics)
Background: Recombinant tissue plasminogen activator (rtPA) remains the standard thrombolytic treatment for ischemic stroke. Different types of nanoparticles have emerged as promising tools to improve the benefits and decrease the drawbacks of this therapy. Among them, cell membrane-derived (CMD) nanomedicines have gained special interest due to their capability to increase the half-life of particles in blood, biocompatibility, and thrombus targeting. In order to update and evaluate the efficacy of these nanosystems, we performed a meta-analysis of the selected in vivo preclinical studies. Methods: Preclinical in vivo studies in ischemic stroke models have been identified through a search in the Pubmed database. We included studies of rtPA-nanoparticles, which assessed infarct volume and/or neurological improvement. Nanosystems were compared with free (non-encapsulated) rtPA treatment. Standardized mean differences were computed and pooled to estimate effect sizes for lesion volumes and neurological scores. Subgroup analyses by the risk of bias, type of nanoparticle, and time of administration were also performed. Results: A total of 18 publications were included in the meta-analysis. This was based on defined search inclusion criteria. Our analysis revealed that rtPA-nanoparticles improved both lesion volume and neurological scores compared with the free rtPA treatment. Moreover, CMD nanomedicines showed better evolution of infarct volume compared to the other nanoparticles. Funnel plots of lesion volume exhibited asymmetry and publication bias. Heterogeneity was generally high, and the funnel plot and Egger test showed some evidence of publication bias that did not achieve statistical significance in the trim-and-fill analysis. Conclusions: rtPA-encapsulating nanosystems were shown to decrease infarct volume and improve neurological scales compared to the standard treatment, and CMD nanomedicines had the greatest beneficial effect.